Figure drawing for concept artists - Muftic, Kan, 1976- (Worcester, UK. : 3dtotal Publishing, 2017)
"... celebrates the common ground between traditional life drawing and the fast-paced world of the concept art industry. Learn about the skills, techniques, and mindset needed to make successful life drawings, how to capture the forms of the human body on paper, and how to improve your character and concept art with a dynamic approach to figures and anatomy." --back cover.
Keywords: Figure drawing -- Technique; Human figure in art -- Technique; Drawing -- Character development